The Influence of Periodontal Status, IL-ß Level, and PMN Phagocytic Function as Risk Factors on Type 2 Diabetes Mellitus Patients - Oedijani Santoso; Siti Wuryan Prayitno (Faculty of Dentistry, Universitas Indonesia, 2015)
Periodontal status is a periodontal condition evaluated by using plaque index, calculus index, gingival index and pocket index. The main mediator of periodontium inflammation is IL-1ß examined by ELISA method. There is an elevation of PMNs in periodontium inflammation, but the leucotoxin as well as the protease in turn lowers the PMN phagocytic function. Phagocytic function ws measured by flowcytometry. The aim of the study was to evaluate the high risk factors of being type 2 DM. A diagnostic study was conducted by using cross-sectional design on 45 controlled DM (CDM) subjects, 45 uncontrolled DM (UCDM) subjects in the Metabolic Endocrinology Clinic Cipto Mangunkusumo Hospital Jakarta, as compared to 45 non-DM control subjects. The result of multivariate analysis showed that patients of older age (>54 years old), low periodontium status (periodontal index >1.80), high IL-1ß level (>23.70 pg/mL), and low PMN phagocytic function <53.47%), were significantly at high risk of having DM compared to non-DM (p<0.05). Lower periodontium status showed an increase in IL-1ß level, decrease PMN phagocytic function, and consequently, an increase in the risk of being type 2 DM.